DO LAMBDA AO BAZINGA! Transformações e recriações culturais no universo Nerd - ROCHA, ANDERSON ALVES DA (2020)
The nerd culture represents a set of rites, practices, signs and languages that, since their origin, have been articulated by the media. The representation of this culture is directly linked to the environment of production and consumption and to the historical moment in which its characters and plots are shown. It is possible to see the transformations of nerdy culture, its media representations and its stories and characters in two cuts in time, through the analysis of media productions that intend to represent it. Thus, the objective of this work is to investigate the aspects that identify nerdy culture in two audiovisual works: the movie Revenge of the Nerds (1984) and the series The Big Bang Theory (2007 - 2019), what are their representations through the characters, stories and situations, which texts demonstrate the elements of this culture, and from these objects reflect how the nerdy culture has been transformed, creating new meanings and representations, hybridizing new elements and texts around it, as an object of media culture. The assumption is that every culture is dynamic and is always in transformation, as its fundamental characteristic, whether through contact with other cultures, or through the transformations inherent to each society at each distinct moment. To discuss these ideas, the work will be based on the studies of Semiotics of Culture and also on Cultural Studies as a theoretical framework. Initially, the research will focus on the fundamental concepts of culture, its relationship with mass and media communication and its forms of (re) signification, based on the ideas of cultural semiosphere and translation defended by Iuri Lótman. In the sequence, the proposal is to present a definition and a history about the concept of nerd and about its culture.